2013
DOI: 10.1111/cea.12002
|View full text |Cite
|
Sign up to set email alerts
|

The 5‐lipoxygenase‐activating protein inhibitor, GSK2190915, attenuates the early and late responses to inhaled allergen in mild asthma

Abstract: GSK2190915 shows potential as a treatment for patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
(63 reference statements)
2
32
0
Order By: Relevance
“…GATA3 is also expressed in mast cells, 41 eosinophils, 43 and airway epithelial cells, where it controls type 2 cytokine expression and effector mechanisms associated with the allergen-induced allergic response. 44,45 After an allergen challenge, the early asthmatic response depends on mast-cell degranulation, whereas the late asthmatic response is considered to be preferentially T-cell dependent and accompanied by a marked influx of eosinophils into the airways and the airway lumen. Mast-cell tryptase represents a reliable and robust marker of mast-cell activation and mast-cell degranulation.…”
mentioning
confidence: 99%
“…GATA3 is also expressed in mast cells, 41 eosinophils, 43 and airway epithelial cells, where it controls type 2 cytokine expression and effector mechanisms associated with the allergen-induced allergic response. 44,45 After an allergen challenge, the early asthmatic response depends on mast-cell degranulation, whereas the late asthmatic response is considered to be preferentially T-cell dependent and accompanied by a marked influx of eosinophils into the airways and the airway lumen. Mast-cell tryptase represents a reliable and robust marker of mast-cell activation and mast-cell degranulation.…”
mentioning
confidence: 99%
“…More recently, a 5-lipoxygenase–activating protein (FLAP) (Fig. 1) inhibitor (GSK2190915) has been shown to be effective in inhibiting allergic responses to inhaled allergen in patients with mild asthma (Kent et al, 2013). The continued development and refinement of compounds that modulate receptors and signaling associated with mast cell-derived lipid mediators will continue to aid in the treatment of human disease and our understanding of the biology these molecules influence.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, double-blind, crossover design, 19 males with mild asthma were enrolled and they received either GSK2190915 or placebo for 5 days. The early and late asthma response to inhaled allergen challenge measured with the fall in the FEV1 (L) was evaluated and it was found that the active treatment significantly reduced the early asthma response (0 --2 h post-challenge value of the FEV1), treatment difference 0.408 l versus placebo between brackets, treatment difference over placebo 0.229 l. The active treatment was also found to significantly reduce the allergen-induced sputum eosinophil count and the sputum LTB4 levels [30].…”
Section: Flap Inhibitorsmentioning
confidence: 99%